O ESTATUTO DA CIDADE NA PROMOÇÃO DA PARTICIPAÇÃO CIDADÃ: CONSELHOS E O DECRETO N. 9.759/2019 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The article seeks to demonstrate the importance of Councils, instituted by the City Statute and, the democratic threat that they suffer from the publication of Decree 9.759/19. The Councils represent a space for dialogue between society and the Public Administration, compounds by members of sectors from all areas and responsible for passing on to society the demands of society and fighting for them to be met. It is due to this participatory space that the Councils show themselves as important democratic instruments. It so happens that, with the edition of Decree 9.759/2019, which determined the extinction of all Councils, Committees and Commissions of a federal scope that have a significant presence of civil society in their participation, until June 28, 2019. This determination was partially suspended due to the proposal of ADI 6121, still pending judgment and, as a result, the Councils suffer a great threat of extinction. However, the study stands out by demonstrating the importance of repealing Decree 9.759/2019 and maintaining the Councils as they are one of the spaces that society has to demand its needs and, its extinction, would be a major social setback for Brazilian democracy. The research is characterized as being theoretical, and bibliographic and the method of procedure is the deductive one, using historical, sociological and legal material, from books and scientific articles.